AON-mediated Exon Skipping Restores Ciliation in Fibroblasts Harboring the Common Leber Congenital Amaurosis CEP290 Mutation - Xavier Gerard; Isabelle Perrault; Sylvain Hanein; Eduardo Silva; Karine Bigot; Sabine Defoort-Delhemmes; Marlèene Rio; Arnold Munnich; Daniel Scherman; Josseline Kaplan; Antoine Kichler; Jean-Michel Rozet (Elsevier, 2012)
Leber congenital amaurosis (LCA) is a severe hereditary retinal dystrophy responsible for congenital or early-onset blindness. The most common disease-causing mutation (>10%) is located deep in intron 26 of the CEP290 gene (c.2991+1655A>G). It creates a strong splice donor site that leads to insertion of a cryptic exon encoding a premature stop codon. In the present study, we show that the use of antisense oligonucleotides (AONs) allow an efficient skipping of the mutant cryptic exon and the restoration of ciliation in fibroblasts of affected patients. These data support the feasibility of an AON-mediated exon skipping strategy to correct the aberrant splicing.